Domesticating and Glocalising the Dreamy: McCay’s Little Nemo and Its Sequels in Early Italian Corriere dei Piccoli (1909-1914) - Eva Van de Wiele (Interfaces)
The editors of Corriere dei Piccoli (CdP), an Italian comics magazine for children launched in December 1908, followed the New York Herald’s every step. In envisioning the creation of a children’s supplement, Italy’s biggest newspaper understood the enthralment and economic potential of the Sunday pages and introduced its Italian readers to various American serial figures. One of those recurring characters, Winsor McCay's Little Nemo, was the most heavily reformatted on CdP’s centre pages in 1913. The drastic flattening of McCay’s vertical appeal to a double page put the graphic designer to the limits of his possibilities. This domestication of the American format is a consequence of the pedagogical ideas and moralistic intentions behind the bourgeois magazine, and Italian style and reading preferences related to readership. Still, Little Nemo inspired the autochthonous authors to create their own versions of McCay’s serial narrative. I uncover the actualizations of the serial figure by three Italian comic artists, unveiling the many moralistic and propagandistic incarnations of Little Nemo. Although heavily reformatted, Little Nemo’s legacy in CdP went further than any other Sunday page.